Habitat–performance relationships of a large mammal on a predator‐free island dominated by humans - Andrew M. Allen; Augusta Dorey; Jonas Malmsten; Lars Edenius; Göran Ericsson; Navinder J. Singh (Ecology and Evolution, 2017)
Abstract The demographic consequences of changes in habitat use driven by human modification of landscape, and/or changes in climate, are important for any species. We investigated habitat–performance relationships in a declining island population of a large mammal, the moose (Alces alces), in an environment that is predator‐free but dominated by humans. We used a combination of demographic data, knowledge of habitat selection, and multiannual movement data of female moose (n = 17) to understand how space use patterns affect fecundity and calf survival. The calving rate was 0.64 and was similar to calving rates reported in other populations. Calf survival was 0.22 (annually) and 0.32 (postsummer), which are particularly low compared to other populations where postsummer survival is typically above 0.7. Home ranges were mainly composed of arable land (>40%), and selection for arable land was higher in winter than in summer, which contrasts with previous studies. Females that spent more time in broadleaf forest in the summer prior to the rut had higher fecundity rates, while more time spent in arable land resulted in lower fecundity rates. Females that spent more time in thicket/scrubland habitats during winter had lower calf survival, while females that had higher use of mixed forests tended to have higher calf survival. The dominance, and subsequent use, of suboptimal foraging habitats may lead to poor body condition of females at parturition, which may lower calf body weights and affect the mother's ability to lactate. In addition, our results indicated that the growing season has advanced significantly in recent decades, which may be causing a mismatch between parturition and optimal resource availability. These effects may exacerbate the female's ability to meet the energetic demands of lactation. Therefore, the observed low calf survival appears to be caused by a combination of factors related to current land use and may also be due to changing vegetation phenology. These results have important implications for the management of species in human‐dominated landscapes in the face of climate change, and for an increased understanding of how species may adapt to future land use and climate change.